2017
DOI: 10.1038/aps.2017.78
|View full text |Cite
|
Sign up to set email alerts
|

ABT-263 induces G1/G0-phase arrest, apoptosis and autophagy in human esophageal cancer cells in vitro

Abstract: Both the anti- and pro-apoptotic members of the Bcl-2 family are regulated by a conserved Bcl-2 homology (BH3) domain. ABT-263 (Navitoclax), a novel BH3 mimetic and orally bioavailable Bcl-2 family inhibitor with high affinity for Bcl-xL, Bcl-2 and Bcl-w has entered clinical trials for cancer treatment. But the anticancer mechanisms of ABT-263 have not been fully elucidated. In this study we investigated the effects of ABT-263 on human esophageal cancer cells in vitro and to explore its anticancer mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…In addition, AZD1775 sensitizes acute myelogenous leukemia to cytarabine, medulloblastoma cell lines to cisplatin, and high-grade glioma cell lines to irradiation, independently of p53 functionality (Porter et al, 2012; Harris et al, 2014; Mueller et al, 2014). Recently, Hauge S et al reported that the p21 (a downstream target of p53)-deficient cancer cells are more sensitive to AZD1775 alone or in combination with ionizing radiation (Hauge et al, 2019), whereas both cell lines used in this study have been demonstrated to express p21 (Lin et al, 2017; Liu et al, 2018). Collectively, these findings suggest that whether the status of p53 or p21 is predictive of AZD1775 response largely depends on the types of cancer.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, AZD1775 sensitizes acute myelogenous leukemia to cytarabine, medulloblastoma cell lines to cisplatin, and high-grade glioma cell lines to irradiation, independently of p53 functionality (Porter et al, 2012; Harris et al, 2014; Mueller et al, 2014). Recently, Hauge S et al reported that the p21 (a downstream target of p53)-deficient cancer cells are more sensitive to AZD1775 alone or in combination with ionizing radiation (Hauge et al, 2019), whereas both cell lines used in this study have been demonstrated to express p21 (Lin et al, 2017; Liu et al, 2018). Collectively, these findings suggest that whether the status of p53 or p21 is predictive of AZD1775 response largely depends on the types of cancer.…”
Section: Discussionmentioning
confidence: 69%
“…ABT 263 (Navitoclax) is a chemotherapy drug that is used to induce apoptosis in cervical, esophageal, leukemia, and lung cancer cells by inhibiting the antiapoptotic proteins, Bcl-2 and Bcl-xL [35][36][37][38]. ABT 263 was shown to selectively clear senescent cells in vivo through inhibition of Bcl proteins [39-41] and to diminish SASP [42].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have verified that ABT-263 can induced autophagy by increasing LC3-II level and suppressing p62 [20]. Although it is known that inhibition of Bcl2 can induce autophagy [21], the mechanism are still controversial.…”
Section: Discussionmentioning
confidence: 99%